MENINGKATKAN AKTIVITAS, KERJA SAMA, DAN HASIL BELAJAR MURID KELAS IV MUATAN MATEMATIKA MELALUI PENERAPAN MODEL PROBLEM BASED LEARNING DI SDN KELAYAN TIMUR 2 - Yunita, Nisa; Oktavia, Khalida; Ni'mah, Khairatun; Rahmawati, Erma; Amberansyah; Saudah, Masnun (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is against the background by the low activity, cooperation, and learning outcomes of IV students in Mathematics at SDN Kelayan Timur 2. The cause is one-way, conventional learning and does not provide space for students to work together. Efforts to overcome this are by using the Problem Based Learning model. The purpose of this research is to improve student activity, cooperation, and learning outcomes. This research is a Classroom Action Research (CAR) which is carried out collaboratively in two cycles. The subjects of the research are 25 grade IV students of SDN Kelayan Timur 2. The type of research used is qualitative and quantitative data. Data collection techniques use observation, learning outcome tests, and documentation. Data analysis uses comparative descriptive techniques by comparing the results of the pre-cycle, cycle I, and cycle II. The results of the study show a significant increase in all aspects. In the pre-cycle, only 44% of students were active, 44% of students cooperated, and the completion of learning outcomes was only 40%. After cycle I, student activity increased to 52%, cooperation to 56%, and the completion of learning outcomes to 52%. In cycle II, student activity and cooperation each reached 92%, and the learning outcome completion reached 88%. It was concluded that the implementation of the Problem Based Learning model effectively increased the activity, cooperation, and learning outcomes of fourth-grade students in Mathematics at SDN Kelayan Timur 2.